Existence of Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 108/DSN-MUI/X/2016 Concerning Guidelines for Organizing Tourism Based on Sharia Principles: Between Spiritual and Regulatory - Novea Elysa Wardhani (Journal of Social Research, 2023)
The halal tourism industry, a significant sector in Indonesia, hinges on a harmonious blend of sharia principles and national legislation. This dual regulatory framework plays a pivotal role in ensuring the industry's robust growth while adhering to cultural values and legal safeguards. Sharia law, represented by fatwas (Islamic rulings), is a foundational element in halal tourism. These principles encompass various aspects, such as halal food, modest dress codes, and ethical behavior, aligning with the cultural and religious expectations of Muslim travelers. To fortify this alignment with the legal structure, it's crucial to integrate these fatwas into positive law, the national legal framework. This integration achieves several vital objectives. First, it establishes a legal foundation for the halal tourism industry, giving it a solid footing within the broader legal context of the country. Second, it enhances transparency, ensuring that halal tourism operators and tourists alike understand the rules and expectations, thereby fostering trust and credibility. Third, it ensures that the industry remains compliant with both Sharia values and national regulations, leading to a more sustainable and inclusive sector. The ultimate goal is to create a halal tourism industry that not only caters to the needs of Muslim travelers but also upholds legal standards, protects consumer rights and contributes positively to the nation's economy and cultural heritage. By synergizing Sharia principles with national legislation, Indonesia can pave the way for a dynamic and legally secure halal tourism industry that benefits both its people and its image on the global stage.